К истории изучения Ольвии в первой трети XIX в. - Тункина, И.В. (Археологія, 2001)
Статья посвящена исследованию Ольвии в первой трети XIX в. В то время были составлены первые планы древнего города и его округи, опубликованы первые результаты научных исследований по истории памятника, введены в научный обиход новые надписи и монеты, происходившие из Ольвии. В історії вивчення Ольвії ключовою для XIX ст. можна вважати першу третину сторіччя, коли було знято перші плани городища та його околиць, написано перші наукові дослідження по її історії, введено в науковий обіг десятки невідомих раніше написів та монетних типів. І хоча дослідження того часу ще не набули систематичного і строго наукового характеру через нерозвиненість російської класичної археології, яка робила ще перші кроки, вони вже тоді привертали увагу освічених прошарків російського суспільства, вихованого на ідеалах класицизму. In the history of the study of Olbia, the first quarter of the XIX century is rightfully considered to be the key moment: the first plans of the ancient town and its environs were made, the first scientific works on its history were written, dozens of the inscriptions and coin types unknown before were put into scientific circulation. Despite the fact, that the investigations of that time hadn't yet gained strictly scientific character through the lack of development of Russian classical archaeology, which was only making its first steps, still they managed to attract the attention of the educated strata of Russian society, brought up on the ideals of classicism and worshiping the immortal beauty of antiquity.